2017
DOI: 10.1186/s40677-017-0068-y
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the risk of tsunami in a context of high-level risk assessment and management: the case of the fjord Lyngen in Norway

Abstract: Background: North Norway, the banks of the fjord Lyngen are highly exposed to a rockslide tsunami hazard. However, the local municipality believes that the coastal community is well-informed about the risk and ready to evacuate, should a warning be issued. Accordingly, the social survey we conducted in this municipality was a matter of exploring three main questions: is the Lyngen population well-informed about the tsunami risk in general and about the potential evacuation time in particular? Is the local popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…We are focusing on coastal flooding risk as it remains misunderstood from the viewpoint of its appraisal by the public and the type of protection/adaptation action envisaged (Flanquart, 2012). Indeed, research studies show that inhabitants of exposed areas tend to underestimate this risk (Goeldner-Gianella et al, 2017; Michel-Guillou & Meur-Ferec, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We are focusing on coastal flooding risk as it remains misunderstood from the viewpoint of its appraisal by the public and the type of protection/adaptation action envisaged (Flanquart, 2012). Indeed, research studies show that inhabitants of exposed areas tend to underestimate this risk (Goeldner-Gianella et al, 2017; Michel-Guillou & Meur-Ferec, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…According to Slovic (1987), "studies of risk perception examine the judgments people make when they are asked to characterize and evaluate hazardous activities and technologies". Thus an individual's perception could be different from expert assessment of hazard or risk for many reasons including the difficulties of assessing probabilities of hazard, because of a lack of information about the risk (Botzen et al 2009;Heitz and Shimabuku 2017) or because a lack of confidence in the authorities (Goeldner-Gianella et al 2017). Individuals' perception of risk has been widely studied using different methodologies of surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Cahyanto and Pennington-Gray (2015) discuss how the role of gender, residence, and past experience with hurricanes affects tourists' voluntary evacuation in such events. Tourist behavior is assessed based on surveys and stated preferences models in Goeldner-Gianella et al (2017) and Matyas et al (2011), which show that tourists behave differently than residents. As an example, a review of the literature on evacuation from natural disasters was conducted by Thompson et al (2017), who identified about 80 independent articles, some of them regarding tourist behavior during disasters.…”
Section: Introductionmentioning
confidence: 99%
“…Cahyanto and Pennington-Gray (2015) discuss how the role of gender, residence, and past experience with hurricanes affects tourists’ voluntary evacuation in such events. Tourist behavior is assessed based on surveys and stated preferences models in Goeldner-Gianella et al. (2017) and Matyas et al.…”
Section: Introductionmentioning
confidence: 99%